2020
DOI: 10.1109/jlt.2020.2984464
|View full text |Cite
|
Sign up to set email alerts
|

Bragg reflection and conversion between helical Bloch modes in chiral three-core photonic crystal fiber

Abstract: Optical fiber modes carrying orbital angular momentum (OAM) have many applications, for example in modedivision-multiplexing for optical communications. The natural guided modes of N-fold rotationally symmetric optical fibers, such as most photonic crystal fibers, are helical Bloch modes (HBMs). HBMs consist of a superposition of azimuthal harmonics (order m) of order A (m) = A (0) + mN. When such fibers are twisted, these modes become circularly and azimuthally birefringent, that is to say HBMs with equal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…ubsequent analysis has revealed that the dispersion relation in Eq. (3) in this paper [1] is incorrect, because it does not take proper account of the transformation from the helicoidal to the cartesian frame. The correct analysis has been reported in detail in a recent paper [2].…”
Section: Erratummentioning
confidence: 89%
“…ubsequent analysis has revealed that the dispersion relation in Eq. (3) in this paper [1] is incorrect, because it does not take proper account of the transformation from the helicoidal to the cartesian frame. The correct analysis has been reported in detail in a recent paper [2].…”
Section: Erratummentioning
confidence: 89%